Educational Counseling Services and Enhancement of Entrepreneurial Skills among Secondary School Students in Bamenda city, North West, Cameroon - Chuo Wung , Catherine; F Wiysahnyuy , Lilian; Sigala , Maxwell (International Journal on Integrated Education, 2025)
One of the core aspects of school counselling is to guide students in relation to the development of entrepreneurial skills which could be beneficial to their daily lives. The purpose of this paper was to assess the influence of educational counseling services like orientation and information services on enhancement of entrepreneurial skills among secondary school students in Bamenda city. The research design used in this study was the concurrent nested design. Qualitative data collected from 11 school counselors through the Educational Counseling and Entrepreneurship Interview Guide (ECEIG), were used to substantiate the quantitative data from 395 secondary high school students gotten through the Educational Counseling and Entrepreneurship Questionnaire (ECEQ). Descriptive statistics (in form of frequencies and percentages) and inferential statistics (Chi square, and regression analyses) were used to analyze the quantitative data. Thematic analysis is used to analyze qualitative data and results displayed in tabular and narrative forms. The findings reveal that: majority of the students (78%) received orientation service on entrepreneurial skills from their school counselors. A Chi Square test of association and a binary logistic regression revealed that there was a significant (P-value < 0.001) influence of orientation service on the enhancement of entrepreneurial skills among secondary school students in the Bamenda city. It was also noticed that majority of the students (68%) from the overall findings received information service on entrepreneurial skills from their school counselor. A Chi Square test of association and a binary logistic regression revealed a significant (P-value < 0.001) influence of information service on the enhancement of entrepreneurial skills among secondary school students in the Bamenda city. It is recommended that school administrators in collaboration with counselors should organize official yearly career orientation days and ensure that adequate information on entrepreneurial skills i made available for students.